PENGEMBANGAN MOBILE POCKET BOOK BERBASIS ANDROID PADA STMIK NURDIN HAMZAH JAMBI: MOBILE POCKET BOOK, ANDROID, RAD - Rini, Faiza; Louis, Ahmad; Marapurna, Aditya (FORTECH (Journal of Information Technology), 2020)
This research aimed to develop an Android-based mobile pocket book learning media and can be a supplement in understanding courses. This research uses a rapid application development (RAD) approach. And the source of this research is students who study the analysis and design of the seventh semester information system in the Nurdin Hamzah STMIK study program. To find out that the mobile pocket book application can be accepted by students, the researchers conducted a data collection technique by interviewing 40 student respondents. from 40 students 38 students who expressed interest in using a mobile pocket book. The mobile pocket book is produced in the form of an extension file. The application can be run on Android. Media that are made can give a positive response to students taking courses in the analysis and design of information.